A Hydroalcoholic Extract from the Leaves of Nerium oleander Inhibits Glycolysis and Induces Selective Killing of Lung Cancer Cells - Calderón-Montaño, José Manuel; Burgos-Morón, Estefanía; Orta, Manuel Luis; Mateos, Santiago; López-Lázaro, Miguel (Planta Medica, 2013)
Recent evidence suggests that cardiac glycosides might be used for the treatment of cancer. The ornamental shrub Nerium oleander has been used in traditional medicine for treating several disorders including cancer, and extracts from the leaves of this plant have already entered phase I clinical trials. In this communication, we have prepared a hydroalcoholic extract from the leaves of Nerium oleander (containing 4.75 ± 0.32 % of cardenolides) and have assessed its cytotoxic activity in A549 lung cancer cells vs. MRC5 nonmalignant lung fibroblasts. The results showed that the cytotoxicity of the Nerium oleander extract against the cancer cell line was significantly higher than that against the nonmalignant cell line, with a potency and selectivity similar to those of the anticancer drug cisplatin. Pretreatment of A549 cells with the antioxidants N-acetylcysteine and catalase slightly prevented the cytotoxicity of the extract, therefore suggesting that the formation of reactive oxygen species participates in its cytotoxic activity but does not play a major role. Nerium oleander extract-induced cytotoxicity and DNA damage (gamma-H2AX focus formation) were slightly higher in cells lacking BRCA2 (deficient in homologous recombination repair) than in parental cells; this indicates that the induction of DNA damage may also play a role in the cytotoxicity of the extract. Nerium oleander extract induced a marked inhibition of glycolysis (glucose consumption and lactate production) in A549 cells, comparable to that of the glycolysis inhibitor dichloroacetate (currently in clinical development for cancer therapy). Because platinum compounds are widely used in the treatment of lung cancer, we tested the cytotoxicity of several combinations of cisplatin with the extract and found a moderate synergism when Nerium oleander extract was administered after cisplatin but a moderate antagonism when it was added before cisplatin. Our results suggest that extracts from Nerium oleander might induce anticancer effects in patients with lung cancer and support their possible advancement into phase II clinical trials for the treatment of this type of cancer.
Keywords: Nerium oleander; Apocynaceae; cardiac glycosides; cardiotonic steroids; anticancer